A model for e-healthcare adoption and patient safety - Abdulhussean, Sanaa Abdulkarim (2015)
Information technology (IT) and information systems (IS) were often associated with improved outcomes. Generally, when IT or IS including internet were thoughtfully selected and properly implemented, vulnerability to human fallibility can be reduced. Studies related to adoption of IT and IS in healthcare sector were essential, and this study aimed to explore factors that are crucial to the adoption of electronic healthcare (e-healthcare) and their impacts on patient safety. The secondary data retrieved from past articles were employed and analyzed in this study. The findings of this study were the research model and hypotheses which were developed based on adoption of IT and IS theories, and essential elements of patient safety. A direction for future research was then described.